2014
DOI: 10.1186/1471-2202-15-47
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of antidotes (midazolam, atropine and HI-6) on nerve agent induced molecular and neuropathological changes

Abstract: BackgroundRecent alleged attacks with nerve agent sarin on civilians in Syria indicate their potential threat to both civilian and military population. Acute nerve agent exposure can cause rapid death or leads to multiple and long term neurological effects. The biochemical changes that occur following nerve agent exposure needs to be elucidated to understand the mechanisms behind their long term neurological effects and to design better therapeutic drugs to block their multiple neurotoxic effects. In the prese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 50 publications
0
10
0
2
Order By: Relevance
“…The data reported so far show that midazolam can protect against nerve agent-induced brain damage in adult or young-adult rats, if it is administered at the time of exposure (Chapman et al, 2015), at the onset of seizures (RamaRao et al, 2014), or after 5 min of seizure activity (Gilat et al, 2005); however, if it is given 1 h after exposure, it does not prevent histological damage, despite its antiseizure efficacy and beneficial effects on behavioral performance and inflammatory responses (Chapman et al, 2015). More studies are needed to understand the neuroprotective efficacy of midazolam when administered at different time points after nerve agent exposure, and direct comparisons must be made with LY293558 under the same experimental conditions for two drugs.…”
Section: Evaluation Of Long-term Effects 30 Days After Soman Exposurmentioning
confidence: 98%
“…The data reported so far show that midazolam can protect against nerve agent-induced brain damage in adult or young-adult rats, if it is administered at the time of exposure (Chapman et al, 2015), at the onset of seizures (RamaRao et al, 2014), or after 5 min of seizure activity (Gilat et al, 2005); however, if it is given 1 h after exposure, it does not prevent histological damage, despite its antiseizure efficacy and beneficial effects on behavioral performance and inflammatory responses (Chapman et al, 2015). More studies are needed to understand the neuroprotective efficacy of midazolam when administered at different time points after nerve agent exposure, and direct comparisons must be made with LY293558 under the same experimental conditions for two drugs.…”
Section: Evaluation Of Long-term Effects 30 Days After Soman Exposurmentioning
confidence: 98%
“…Midazolam has been suggested as a better anticonvulsant than diazepam for nerve agent seizures. Midazolam has been tested extensively in a variety of animal models of OP exposure . Most experiments are conducted in a guinea‐pig model that is designed to closely simulate the military antidote regimen (pyridostigmine pretreatment and atropine sulfate + 2‐PAM).…”
Section: Experimental Pharmacology Of Midazolam In Op Modelsmentioning
confidence: 99%
“…Midazolam has been tested extensively in a variety of animal models of OP exposure. 4,43,[55][56][57][58] Most experiments are conducted in a guinea-pig model that is designed to closely simulate the military antidote regimen (pyridostigmine pretreatment and atropine sulfate + 2-PAM). Rat and primate models were also utilized for testing the anticonvulsant therapies for OP intoxication.…”
Section: Experimental Pharmacology Of Midazolam In Op Modelsmentioning
confidence: 99%
“…Midazolam (MDZ) has been proposed as a replacement anticonvulsant to diazepam for OP intoxication (Gilbert et al, 1999;Glauser et al, 2016;Smith and Brown, 2017). MDZ is an effective anticonvulsant in experimental paradigms (McDonough et al, 1999(McDonough et al, , 2009Koplovitz et al, 2001;Capacio et al, 2004;RamaRao et al, 2014). The RAMPART (Rapid Anticonvulsant Medication Prior to Arrival Trial, a NIH-sponsored clinical trial) study showed that MDZ can control SE in outpatient settings (Silbergleit et al, 2011(Silbergleit et al, , 2012.…”
Section: Introductionmentioning
confidence: 99%